Printed Electronics: A Novel Blade‐Jet Coating Method for Achieving Ultrathin, Uniform Film toward All‐Solution‐Processed Large‐Area Organic Light‐Emitting Diodes (Adv. Mater. Technol. 3/2016). Issue 3 (15th June 2016) - Seok, Jae Young; Yang, Minyang
Abstract : Jaeyoung Seok and Minyang Yang propose, in article 1600029, a new type of printing technique for manufacturing multi‐layered thin film devices over a large‐area. By hybridizing the conventional blade‐coating method and air‐jet finishing technique, functional ultra‐thin films with outstanding quality are easily fabricated. This practical and advanced printing method could be widely used for mass production of high‐performance printed electronic devices including OLEDs.